Collimated protons accelerated from an overdense gas jet irradiated by a 1 µm wavelength high-intensity short-pulse laser. Issue 1 (December 2017) - Chen, S.; Vranic, M.; Gangolf, T.; Boella, E.; Antici, P.; Bailly-Grandvaux, M.; Loiseau, P.; Pépin, H.; Revet, G.; Santos, J.; Schroer, A.; Starodubtsev, Mikhail; et al.
Abstract We have investigated proton acceleration in the forward direction from a near-critical density hydrogen gas jet target irradiated by a high intensity (1018 W/cm2 ), short-pulse (5 ps) laser with wavelength of 1.054 μm. We observed the signature of the Collisionless Shock Acceleration mechanism, namely quasi-monoenergetic proton beams with small divergence in addition to the more commonly observed electron-sheath driven proton acceleration. The proton energies we obtained were modest ( MeV), but prospects for improvement are offered through further tailoring the gas jet density profile. Also, we observed that this mechanism is very robust in producing those beams and thus can be considered as a future candidate in laser-driven ion sources driven by the upcoming next generation of multi-PW near-infrared lasers.